Sulfinylation on Superoxide Dismutase 1 Cys111: Novel Mechanism for 1‐Nitropyrene to Promote Acute Reactive Oxygen Species Generation. Issue 3 (10th March 2021) - Xie, Guangshan; Zhu, Lin; Zhang, Yanhao; Song, Yuanyuan; Zhang, Hongna; Yang, Zhu; Cai, Zongwei
Abstract : 1‐Nitropyrene In article number 2000123, Zongwei Cai and co‐workers show that 1‐nitropyrene inhibits superoxide dismutase 1 (SOD1) activity to increase intracellular reactive oxygen species (ROS) by forming cysteine sulfinylation on Cys111 of SOD1. Therefore, a novel mechanism of 1‐nitropyrene‐induced acute cytotoxicity and ROS production is proposed.